Comparison of microwave extraction technique and conventional extraction technique for extracting essential oils from lemongrass, tumeric and ginger - Abd Aziz, Nor Azila (2012)
The purpose of this research is to compare the performance between two techniques of extraction which are Microwave Extraction Technique (MET) and Conventional Extraction Technique (CET) in extracting essential oils from Lemongrass, Ginger and Turmeric by using wet distillation (WD), dry distillation (DD) and hydro distillation (HD) methods in term of efficiency, rapidity, the yield of oil and the quality or composition of oil. The important parameters in the extraction process such as time, temperature and microwave power output were controlled to obtain high yield essential oils. The MET is performed at 450 W of irradiation power and temperature about 100°C for 1 hour using WD and DD. The CET is performed using HD at 450 W of extraction power and temperature 100°C for 4 hours. The absorbed power of microwave irradiation for WD and DD are also estimated to determine the method with higher value of absorbed power. A higher absorbed power means it is more efficient. The MET provides a rapid extraction 4 times faster compared to CET. After 1 hour of extraction using MET, the total yield of essential oils is about the same with 4 hours extraction using CET. During WD, it requires only 8 to 12 minutes to achieve the boiling point of water (100.00±1.00°C) whereas DD requires 8 to 15 minutes. However, HD requires 15 to 17 minutes to achieve the boiling point of water. From the 300.000 ± 0.001g actual weight of Lemongrass, the highest yield of essential oils per second is using the DD method which gives 10.4 ´ 10 -5% compared to WD with 8.97 ´ 10 -5% and DD with 2.09 ´ 10 -5% . It is different with Ginger and Turmeric, the WD method gives them the highest yield of essential oil per second. For Ginger, the total yield of essential oil per second using WD is 3.85 ´ 10 -5% , higher than DD(1.06 ´ 10 -5%) and HD(0.96 ´ 10 -5%). For Turmeric, the total yield per second using WD is 19.79 ´ 10 -5% , which is very high compared to DD with 4.17 ´ 10 -5% and HD with 3.65 ´ 10 -5% . The absorbed power of fresh sample mixture, ( )mfs PA Vol during DD is estimated to be higher than WD and this implies that DD is the more efficient method for the heating process. Another parameter is number of days to soak the samples. Generally, the longer time taken to soak the sample will produce more yields but this depends on the type of sample. Lemongrass and Turmeric gave the highest yield (0.49% and 0.69%) after 3 days of soaking. However it is vice versa for ginger. Ginger gives the highest yield of essential oils (0.14%) without soaking. The chemical component of the samples was identified using GC-MS. From the results, it was found that MET produced good quality of essential oils compared to CET where the oxygenated compound dominated in all the samples used. From the three samples used, Lemongrass is of better quality of essential oil followed by Turmeric and Ginger with oxygenated fraction of 94.73%, 90.56% and 46.69%.